High-strength, high-wear-resistance and anti-corrosion plate as well as preparation process and application thereof

By using high-strength, high-wear-resistant, and anti-corrosion boards in the spliced ​​floor, the board is combined with the composite plate body through a co-extrusion process. The concave and convex alternate structure and through-hole design of the metal plate body solve the problem of joint gaps and thermal expansion of the spliced ​​floor. Cold shrinkage problem, achieving high strength, wear resistance and corrosion resistance.

CN119332898AActive Publication Date: 2025-01-21GUANGDONG QICHENG NEW MATERIAL TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411444628.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2025-01-21
Estimated Expiration
2044-10-15

AI Technical Summary

Technical Problem

The existing spliced ​​floors have problems with connecting gaps, which affects the splicing effect. In addition, traditional wood-plastic floors lack strength, load-bearing capacity, compression and deformation resistance, and are prone to fracture due to thermal expansion and contraction.

Method used

It adopts high-strength, high-wear-resistant and anti-corrosion plate. The plate includes composite plate body and metal plate body, which are formed into an integrated structure through co-extrusion process. The metal plate body extends along the long strip slot direction of the composite plate body to form a concave and convex structure. , the formed concave parts and convex parts are close to the surface of the composite plate body, and the through-hole design makes the plates fit more closely when they expand with heat and contract with cold.

Benefits of technology

It achieves excellent properties such as high strength, high wear resistance, and anti-corrosion, solves the problem of connection gaps, improves the overall flatness and stability of the floor, and avoids the problem of separation of the substrate and lining caused by thermal expansion and contraction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119332898A_ABST
    Figure CN119332898A_ABST
Patent Text Reader

Abstract

The invention provides a high-strength, high-wear-resistance and anti-corrosion plate and a preparation process and application thereof.The high-strength, high-wear-resistance and anti-corrosion plate comprises a base plate and a lining plate embedded in the base plate, the base plate comprises composite plate bodies, and the multiple composite plate bodies are spliced to form a spliced floor. According to the high-strength, high-wear-resistance and anti-corrosion plate as well as the preparation process and application thereof, through innovative designs such as an integrated co-extrusion process, a seamless splicing design and a concave-convex alternate structure of a metal plate body, the high-strength, high-wear-resistance and anti-corrosion plate is applied to spliced plates and can be used for floor paving or wall decoration and the like, and excellent performances such as high strength, high wear resistance and corrosion resistance are realized; the wood-plastic floor has the advantages of being easy to install and maintain, attractive and the like, the problem that the base plate and the lining plate are prone to being separated due to thermal expansion and cold contraction is solved, and meanwhile the common defects that a traditional wood-plastic floor has certain defects in the aspects of structural strength, bearing capacity, compression resistance, deformation resistance and the like, thermal expansion and cold contraction exist, and breakage is prone to occurring are overcome.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building accessories, and in particular to a high-strength, high-wear-resistant and anti-corrosion plate and a preparation process and application thereof. Background Art

[0002] With the development of society, the use of splicing flooring is becoming more and more widespread, and its types are also diverse. Splicing flooring is used in factory laying, outdoor temporary laying, outdoor balcony laying, etc. However, most of the existing splicing floors have certain connection gaps when splicing, and seamless splicing cannot be achieved, which affects the splicing effect. Dust and garbage are easily accumulated in the connection gaps, and even too large connection gaps are easy to trip people, which is very inconvenient.

[0003] Moreover, traditional wood-plastic flooring still has certain deficiencies in its structural strength, bearing capacity, compression and deformation resistance, etc., and it also has the common problems of thermal expansion and contraction and is more prone to breakage.

[0004] Therefore, a high-strength, high-wear-resistant and anti-corrosion plate and its preparation process and application are proposed. Summary of the invention

[0005] The present invention aims to solve the problems raised in the background technology and provides a high-strength, high-wear-resistant and anti-corrosion plate and a preparation process and application thereof.

[0006] The specific technical solutions are as follows:

[0007] A high-strength, high-wear-resistant and anti-corrosion plate, comprising:

[0008] A substrate and a liner embedded in the substrate, wherein:

[0009] The base plate includes a composite plate body, and a plurality of the composite plate bodies are spliced ​​together to form a spliced ​​floor;

[0010] The lining plate comprises a metal plate body, and the metal plate body is formed into an integral structure with the composite plate body through a co-extrusion process;

[0011] A through hole is opened on the surface of the metal plate.

[0012] A long strip groove penetrating through both ends of the composite plate is reserved on one side of the composite plate, and a long strip convex strip is reserved on the other side of the composite plate, and the long strip convex strip can be inserted into the long strip groove by interference fit, and the adjacent composite plates are seamlessly spliced ​​by inserting the long strip convex strip into the long strip groove;

[0013] The metal plate extends along the direction of the long strip slot to form a concave-convex alternating structure, and the formed concave parts and convex parts are respectively close to the upper and lower surfaces of the composite plate body, and the formed concave parts and convex parts do not protrude from the upper and lower surfaces of the composite plate body.

[0014] The above-mentioned high-strength, high-wear-resistant and corrosion-resistant plate, wherein: the composite plate body is evenly reserved with a plurality of through grooves along the direction of the long strip-shaped slot, and the plurality of through grooves are staggered between adjacent recessed portions and raised portions.

[0015] The above-mentioned high-strength, high-wear-resistant and corrosion-resistant plate, wherein: some of the through grooves are circular, elliptical, trapezoidal or square.

[0016] The above-mentioned high-strength, high-wear-resistant and corrosion-resistant plate, wherein: a plurality of evenly arranged separation grooves are reserved at the bottom of the composite plate body, and the length direction of the separation grooves is consistent with the length direction of the long strip slots.

[0017] The above-mentioned high-strength, high-wear-resistant and corrosion-resistant plate, wherein: the cross-sections of the recessed portion and the raised portion perpendicular to the length direction of the long strip slot are both trapezoidal, and through holes are provided on the bottom wall and side walls of the recessed portion and the top wall and side walls of the raised portion.

[0018] Some of the through holes are circular, elliptical, trapezoidal or square.

[0019] The above-mentioned high-strength, high-wear-resistant and corrosion-resistant plate, wherein: the metal plate body is an aluminum alloy plate body, and the thickness of the metal plate body is not less than 1 mm.

[0020] The above-mentioned high-strength, high-wear-resistant and anti-corrosion board, wherein: the composite board body is a wood-plastic composite board body, and the thickness of the composite board body is not less than 4 cm.

[0021] The above-mentioned high-strength, high-wear-resistant and corrosion-resistant plate, wherein: the upper surface of the composite plate body is covered with a wrapping layer through a co-extrusion process, and the wrapping layer is an ASA resin material layer; the raw material used for the ASA resin material layer is Chimei ASA resin PW-997S.

[0022] The present invention also provides a composite board, which comprises the following raw materials in parts by weight:

[0023] 18-20 parts of corn stalks with a particle size of 100-200 mesh, 8-12 parts of wood powder with a particle size of 400-500 mesh, 54-60 parts of modified polypropylene, 12-17 parts of ethylene-vinyl acetate copolymer, 0.6-0.9 parts of silane coupling agent, 1-4 parts of modified filler, 1-3 parts of calcium stearate, 0.2-0.5 parts of antibacterial agent (such as silver ion antibacterial agent, purchased from Nanjing Tianshi Landun Biotechnology Co., Ltd., model: silver ion antibacterial agent-LD904) and 0.1-0.3 parts of antioxidant (such as Irganox1010, BASF).

[0024] The preparation method of modified polypropylene comprises the following steps:

[0025] (1) 1 part by weight of graphene oxide and 100-150 parts by weight of deionized water are mixed, ultrasonically dispersed, 0.2-0.4 parts by weight of silane coupling agent KH560 are added, mixed evenly, heated to 70-75° C., stirred for reaction for 2-3 hours, 0.1-0.2 parts by weight of hydrazine hydrate and 1-1.5 parts by weight of ammonia water are added, and reduction reaction is carried out under stirring for 2-4 hours, filtered and dried to obtain silane-modified reduced graphene oxide;

[0026] (2) Dissolving 22-27 parts by weight of polypropylene in 100-120 parts by weight of xylene at 130-135° C., adding 1-3 parts by weight of silane-modified reduced graphene oxide, stirring and reacting for 5-8 hours under heat preservation conditions, and vacuum drying to obtain modified polypropylene.

[0027] Polypropylene, available from Formosa Plastics (Ningbo) Co., Ltd.; model 1450T.

[0028] Coriolus versicolor is a white rot fungus that can decompose cellulose, hemicellulose and lignin in wood. Coriolus versicolor will cause the strength of the board to decrease. In the prior art, graphene is usually added to the raw materials of wood plastic flooring to improve the antibacterial property, but the graphene is unevenly dispersed, resulting in poor antibacterial and corrosion resistance. The present invention can improve the corrosion resistance of the board by modifying polypropylene. At the same time, the modified polypropylene has better compatibility with other raw materials. However, the waterproof performance of the board under this condition is not good.

[0029] The ethylene-vinyl acetate copolymer includes ethylene-vinyl acetate copolymer A, ethylene-vinyl acetate copolymer B and ethylene-vinyl acetate copolymer C in a weight ratio of 1: (1.2-1.4): (0.5-0.8), the melt index of ethylene-vinyl acetate copolymer A is 7.5 g / 10 min, and the mass percentage of vinyl acetate unit is 26%; the melt index of ethylene-vinyl acetate copolymer A is 25 g / 10 min, and the mass percentage of vinyl acetate unit is 28%; the melt index of ethylene-vinyl acetate copolymer A is 150 g / 10 min, and the mass percentage of vinyl acetate unit is 19%. All are purchased from Formosa Plastics Industry (Ningbo) Co., Ltd.; models are 7470M, 7760H, and 7A50H.

[0030] Waterproofness is a very important property of the board. The water-proofness of the board after polypropylene modification is not ideal. The present invention can improve the water-proofness of the board by adding ethylene-vinyl acetate copolymer on the basis of the raw material containing modified polypropylene. By adding ethylene-vinyl acetate copolymer, a denser network structure can be formed with other components in the system to improve the water-proofness. At the same time, when ethylene-vinyl acetate copolymer is mixed with three ethylene-vinyl acetate copolymers with different parameters in a specific ratio, the boiling water resistance of the board can be improved.

[0031] The modified filler comprises the following steps:

[0032] (1) mixing titanium dioxide, lanthanum oxide and silicon dioxide in a weight ratio of (1.2-1.5):1:(0.3-0.6) to obtain a mixed filler;

[0033] (2) mixing a mixed filler, a silane coupling agent KH560, ethanol and deionized water in a weight ratio of 1: (0.1-0.3): (20-25): (35-40), heating and stirring at 80-85° C. for 3-5 hours, cooling, filtering and washing to obtain a silane-modified mixed filler;

[0034] (3) Mixing a silane-modified mixed filler, nano-polytetrafluoroethylene, polyvinyl pyrrolidone and 40-50% by weight of an ethanol aqueous solution in a weight ratio of 1: (10-15): (0.1-0.4): (60-80), dispersing the mixture evenly, and spray drying the mixture to obtain a modified filler.

[0035] The particle size of the titanium dioxide is 10-20 nm and the specific surface area is 30-100 m 2 / g; the particle size of lanthanum oxide is 30-50nm and the specific surface area is 20-40m 2 / g; the particle size of silicon dioxide is 10-20nm and the specific surface area is 200-250m 2 / g.

[0036] The present invention also provides a process for preparing a high-strength, high-wear-resistant and anti-corrosion plate, comprising the following steps:

[0037] S1: Prepare raw materials for the composite plate (101), including the following raw materials in parts by weight:

[0038] 18-20 parts of corn stalks with a particle size of 100-200 mesh, 8-12 parts of wood powder with a particle size of 400-500 mesh, 54-60 parts of modified polypropylene, 12-17 parts of ethylene-vinyl acetate copolymer, 0.6-0.9 parts of silane coupling agent, 1-4 parts of modified filler, 1-3 parts of calcium stearate, 0.2-0.5 parts of antibacterial agent (such as silver ion antibacterial agent, purchased from Nanjing Tianshi Landun Biotechnology Co., Ltd., model: silver ion antibacterial agent-LD904) and 0.1-0.3 parts of antioxidant (such as Irganox1010, BASF).

[0039] The preparation method of modified polypropylene comprises the following steps:

[0040] (1) 1 part by weight of graphene oxide and 100-150 parts by weight of deionized water are mixed, ultrasonically dispersed, 0.2-0.4 parts by weight of silane coupling agent KH560 are added, mixed evenly, heated to 70-75° C., stirred for reaction for 2-3 hours, 0.1-0.2 parts by weight of hydrazine hydrate and 1-1.5 parts by weight of ammonia water are added, and reduction reaction is carried out under stirring for 2-4 hours, filtered and dried to obtain silane-modified reduced graphene oxide;

[0041] (2) Dissolving 22-27 parts by weight of polypropylene in 100-120 parts by weight of xylene at 130-135° C., adding 1-3 parts by weight of silane-modified reduced graphene oxide, stirring and reacting for 5-8 hours under heat preservation conditions, and vacuum drying to obtain modified polypropylene.

[0042] Polypropylene, available from Formosa Plastics (Ningbo) Co., Ltd.; model 1450T.

[0043] The ethylene-vinyl acetate copolymer includes ethylene-vinyl acetate copolymer A, ethylene-vinyl acetate copolymer B and ethylene-vinyl acetate copolymer C in a weight ratio of 1: (1.2-1.4): (0.5-0.8), the melt index of ethylene-vinyl acetate copolymer A is 7.5 g / 10 min, and the mass percentage of vinyl acetate unit is 26%; the melt index of ethylene-vinyl acetate copolymer A is 25 g / 10 min, and the mass percentage of vinyl acetate unit is 28%; the melt index of ethylene-vinyl acetate copolymer A is 150 g / 10 min, and the mass percentage of vinyl acetate unit is 19%. All are purchased from Formosa Plastics Industry (Ningbo) Co., Ltd.; models are 7470M, 7760H, and 7A50H.

[0044] The modified filler comprises the following steps:

[0045] (1) mixing titanium dioxide, lanthanum oxide and silicon dioxide in a weight ratio of (1.2-1.5):1:(0.3-0.6) to obtain a mixed filler;

[0046] (2) mixing a mixed filler, a silane coupling agent KH560, ethanol and deionized water in a weight ratio of 1: (0.1-0.3): (20-25): (35-40), heating and stirring at 80-85° C. for 3-5 hours, cooling, filtering and washing to obtain a silane-modified mixed filler;

[0047] (3) Mixing a silane-modified mixed filler, nano-polytetrafluoroethylene, polyvinyl pyrrolidone and 40-50% by weight of an ethanol aqueous solution in a weight ratio of 1: (10-15): (0.1-0.4): (60-80), dispersing the mixture evenly, and spray drying the mixture to obtain a modified filler.

[0048] The particle size of the titanium dioxide is 10-20 nm and the specific surface area is 30-100 m 2 / g; the particle size of lanthanum oxide is 30-50nm and the specific surface area is 20-40m 2 / g; the particle size of silicon dioxide is 10-20nm and the specific surface area is 200-250m 2 / g.

[0049] The use of a highly wear-resistant composite plate body in conjunction with a metal plate can improve the overall durability and aesthetics of the floor, and can also improve the structural stability and installation convenience of the floor, which is more suitable for application scenarios that require higher strength and longer life. The present invention attempts to add fillers to improve the wear resistance of the composite plate body, but the effect is not ideal. However, the compatibility of the filler with other components in the system is poor. The present invention modifies the filler to improve the wear resistance of the plate. The modified filler has better compatibility with other components in the system, higher dispersibility, and a denser structure is formed, which can improve the wear resistance of the plate.

[0050] S2: preparing a raw material of a metal plate, that is, preparing a long strip of aluminum alloy plate having a recessed portion, a raised portion, and a through hole;

[0051] S3: Design a forming mold, wherein the forming mold has a composite plate forming cavity inside, and a cover plate is detachably installed at one end of the forming mold, the cover plate is used to block one end of the composite plate forming cavity, and the cover plate has a slot for inserting a long strip of aluminum alloy plate, a feed pipe is fixedly installed on the outer wall of the forming mold through a plurality of evenly arranged connecting pipes, the feed pipe is connected with the interior of the composite plate forming cavity through the plurality of connecting pipes, and a flange connected with the interior of the feed pipe is fixedly installed on the feed pipe;

[0052] S4: Assembling the molding die and the extruder, and fixing the flange to the extrusion head of the extruder by bolts;

[0053] S5: the raw materials of the composite board body (101) in step S1 are mixed uniformly by a mixer, and then the uniformly mixed raw materials are melt-blended and granulated by a twin-screw extruder to obtain wood-plastic composite granules;

[0054] S6: adding the wood-plastic composite pellets prepared in step S5 into the extruder in step S4 and heating and melting them to a suitable temperature, inserting one end of the long strip aluminum alloy plate into the composite plate forming cavity inside the forming mold through the slot, and then using the extruder to squeeze the molten raw material into the feed pipe and then into the composite plate forming cavity inside the forming mold through a number of evenly arranged connecting pipes;

[0055] S7: After the raw materials in the composite board forming cavity are formed, the cover plate is removed, and then the formed wood-plastic composite board body is taken out together with the long strip aluminum alloy board body, and is quickly cooled and formed by a cooling device to keep its shape and size stable;

[0056] S8: Subsequent processing: Cutting, trimming and subsequent processing are performed as needed to obtain finished high-strength, high-wear-resistant and anti-corrosion plates;

[0057] S9: Inspection and packaging: Carry out quality inspection on finished products, including appearance, size, and mechanical performance indicators. After passing the inspection, they will be packaged and put into storage.

[0058] The present invention also provides an application of a high-strength, high-wear-resistant and corrosion-resistant plate, which is applied to splicing plates and can be used for flooring or wall decoration, etc.

[0059] The present invention has the following beneficial effects:

[0060] The high-strength, high-wear-resistant, anti-corrosion plate and its preparation process and application provided by the present invention achieve excellent properties such as high strength, high wear resistance and anti-corrosion through innovative designs such as integrated co-extrusion process, seamless splicing design and concave-convex alternating structure of metal plate body, and have the advantages of easy installation, easy maintenance and beautiful appearance, etc., and can solve the problem that dust and garbage are easily accumulated in the connection gaps of traditional wood-plastic flooring, and even too large connection gaps are easy to trip people, which is very inconvenient. At the same time, it makes up for the fact that traditional wood-plastic flooring still has certain deficiencies in its own structural strength, bearing capacity, compression and deformation resistance, etc., as well as the common problems of thermal expansion and contraction and easy fracture.

[0061] The present invention provides through holes on the metal plate body, and part of the raw materials of the composite plate body can be embedded in the through holes provided on the metal plate body and formed during extrusion molding. When the plate undergoes thermal expansion and contraction, the base plate and the lining plate will also be firmly connected and will not separate, thus solving the problem that the base plate and the lining plate are easily separated due to thermal expansion and contraction. Specifically, the present invention provides through holes on the metal plate body, and part of the raw materials of the composite plate body can be embedded in the through holes provided on the metal plate body and formed during extrusion molding. On the one hand, it helps to reduce the weight of the metal plate body, and on the other hand, when the composite plate body will produce thermal expansion and contraction deformation under temperature changes, the plate body material corresponding to the through hole position will be embedded in the through hole, so that the composite plate body and the metal plate body are more closely embedded, thus solving the problem that the base plate and the lining plate are easily separated due to thermal expansion and contraction. This is a major breakthrough in the industry and fills the gap in the industry. BRIEF DESCRIPTION OF THE DRAWINGS

[0062] Figure 1 Schematic diagram of the structure of the high-strength, high-wear-resistant, anti-corrosion plate provided in Example 1 of the present invention Figure 1 ;

[0063] Figure 2 Schematic diagram of the structure of the high-strength, high-wear-resistant, anti-corrosion plate provided in Example 1 of the present invention Figure 2 ;

[0064] Figure 3 A schematic diagram of a half-section structure of a high-strength, high-wear-resistant, anti-corrosion plate provided in Example 1 of the present invention;

[0065] Figure 4 A schematic diagram of the structure of the explosion of the high-strength, high-wear-resistant and anti-corrosion plate provided in Example 1 of the present invention;

[0066] Figure 5 Schematic diagram of the structure of the high-strength, high-wear-resistant, anti-corrosion plate provided in Example 1 of the present invention Figure 3 ;

[0067] Figure 6 A schematic structural diagram of a combination of a forming die and a metal plate provided in Example 2 of the present invention;

[0068] Figure 7 A schematic diagram of the exploded structure of a forming die and a metal plate provided in Example 2 of the present invention;

[0069] Figure 8 A schematic diagram of the structure of a high-strength, high-wear-resistant, anti-corrosion plate provided in Example 3 of the present invention;

[0070] Fig. 9 Schematic diagram of the test product of the high-strength, high-wear-resistant and anti-corrosion plate provided by the present invention Figure 1 ;

[0071] Fig.10 Schematic diagram of the test product of the high-strength, high-wear-resistant and anti-corrosion plate provided by the present invention Figure 2 .

[0072] Reference numerals:

[0073] 1. Base plate; 101. Composite plate body; 102. Long strip card slot; 103. Long strip convex strip; 104. Through slot; 105. Separation slot;

[0074] 2. lining plate; 201. metal plate body; 202. recessed portion; 203. raised portion; 204. through hole;

[0075] 3. Wrapping layer;

[0076] 4. Molding mold; 401. Connecting pipe; 402. Feed pipe; 403. Flange; 404. Cover plate; 405. Slot;

[0077] 5. Solid substrate; 501. Trapezoidal groove. DETAILED DESCRIPTION

[0078] The technical solution of the present invention is further described below with reference to the accompanying drawings and through specific implementation methods.

[0079] Example 1

[0080] The high-strength, high-wear-resistant, and anti-corrosion plates provided in this embodiment are Figure 1-Figure 5 As shown, it includes: a substrate 1 and a liner 2 embedded in the substrate 1, wherein:

[0081] The base plate 1 includes a composite plate body 101, and a plurality of composite plate bodies 101 are spliced ​​together to form a spliced ​​floor;

[0082] The liner 2 includes a metal plate body 201, and the metal plate body 201 is formed into an integral structure with the composite plate body 101 through a co-extrusion process;

[0083] A long strip groove 102 is reserved on one side of the composite plate 101 and runs through both ends thereof, and a long strip convex strip 103 is reserved on the other side of the composite plate 101. The long strip convex strip 103 can be inserted into the long strip groove 102 by interference fit. Adjacent composite plates 101 are seamlessly spliced ​​by inserting the long strip convex strip 103 into the long strip groove 102.

[0084] The metal plate 201 extends along the direction of the long slot 102 to form a concave-convex structure. The formed concave portion 202 and convex portion 203 are respectively close to the upper and lower surfaces of the composite plate 101, and the formed concave portion 202 and convex portion 203 do not protrude from the upper and lower surfaces of the composite plate 101.

[0085] The high-strength, high-wear-resistant and anti-corrosion plates using the above technical solution are as follows:

[0086] Integrated co-extrusion process:

[0087] The composite plate body 101 and the metal plate body 201 are formed into an integral structure through a co-extrusion process, which allows the two to be tightly combined, avoiding the delamination or falling off problems that may be caused by traditional adhesives, thereby improving the overall strength and durability.

[0088] Seamless stitching design:

[0089] The design of the long strip groove 102 and the long strip convex strip 103 reserved on the composite board body 101 enables the adjacent composite boards to be seamlessly spliced ​​through interference fit. This design not only simplifies the installation process, but also improves the overall flatness and stability of the floor.

[0090] The concave and convex structure of the metal plate:

[0091] The metal plate 201 extends along the long strip slot 102 to form a concave-convex structure. This design increases the surface area of ​​the metal plate without affecting the surface flatness of the composite plate, thereby improving the bonding strength with the composite plate. At the same time, this structure also helps to disperse stress and improve the overall anti-deformation ability.

[0092] Easy installation and maintenance:

[0093] The seamless splicing design makes the installation process easier and faster, reducing installation time and cost. At the same time, since the panels are tightly connected, gaps and looseness are not easy to occur, reducing the difficulty and cost of maintenance.

[0094] Aesthetics:

[0095] Although the concave and convex structure of the metal plate does not protrude from the surface of the composite plate, it can increase the three-dimensional sense and layering of the plate to a certain extent, and enhance the overall aesthetics. At the same time, the seamless splicing design also ensures the flatness and consistency of the floor surface.

[0096] In summary, the high-strength, high-wear-resistant and anti-corrosion board has achieved excellent performance such as high strength, high wear resistance and anti-corrosion through innovative designs such as integrated co-extrusion process, seamless splicing design and concave-convex alternating structure of metal plate body, and has the advantages of easy installation, easy maintenance and beautiful appearance. It can solve the problem that dust and garbage are easily accumulated in the connection gaps of traditional wood-plastic flooring, and even too large connection gaps are easy to trip people, which is very inconvenient. At the same time, it makes up for the shortcomings of traditional wood-plastic flooring in its own structural strength, bearing capacity, compression and deformation resistance, etc., as well as the common problems of thermal expansion and contraction and easy fracture.

[0097] Specifically, in the present embodiment, in order to save the material cost of the composite plate body 101, a plurality of through grooves 104 are evenly reserved in the composite plate body 101 along the direction of the long strip slot 102, and the plurality of through grooves 104 are staggered between adjacent recessed portions 202 and raised portions 203. In addition, the staggered arrangement of the plurality of through grooves 104 helps to enhance the flexibility of the composite plate body 101, while reducing the overall weight without reducing the strength.

[0098] Specifically, in the present embodiment, the plurality of through grooves 104 are all circular, elliptical, trapezoidal or square in shape. The through grooves of circular, elliptical, trapezoidal or square shapes can be optimized and selected according to specific application requirements to achieve the best effect.

[0099] Specifically, in this embodiment, a plurality of evenly arranged dividing grooves 105 are reserved at the bottom of the composite board body 101, and the length direction of the dividing grooves 105 is consistent with the length direction of the long strip grooves 102. The provided dividing grooves 105 can further enhance the structural stability of the composite board body 101 and reduce deformation caused by temperature changes or stress concentration. The length direction thereof is consistent with the long strip grooves 102, which helps to maintain the overall flatness and strength of the floor.

[0100] Specifically, in this embodiment, the cross-sections of the concave portion 202 and the convex portion 203 perpendicular to the length direction of the long strip slot 102 are both trapezoidal, and through holes 204 are provided on the bottom wall and side walls of the concave portion 202 and the top wall and side walls of the convex portion 203. The trapezoidal cross-section design increases the contact area between the metal plate body 201 and the composite plate body 101, thereby improving the bonding strength.

[0101] As one of the core innovations of the present invention, the through hole 204 is opened on the metal plate 201, which helps to reduce the weight of the metal plate on the one hand, and on the other hand, when the composite plate will produce thermal expansion and contraction deformation under temperature changes, the plate material corresponding to the through hole 204 will be embedded in the through hole 204, so that the composite plate 101 and the metal plate 201 are more tightly embedded, which solves the problem of the composite plate 101 and the metal plate 201 being separated from each other due to thermal expansion and contraction in the existing problem. It is a major breakthrough in the industry and fills the gap in the industry.

[0102] Specifically, in this embodiment, the metal plate 201 is an aluminum alloy plate, and the thickness of the metal plate 201 is not less than 1 mm. Aluminum alloy is selected as the material of the metal plate 201 not only because it has high strength and corrosion resistance, but also because it has good processability and recyclability. The design of a thickness of not less than 1 mm ensures that the metal plate can provide sufficient support and protection without being too bulky.

[0103] Specifically, in this embodiment, the composite board 101 is a wood-plastic composite board, and the thickness of the composite board 101 is not less than 4 cm. The wood-plastic composite board combines the beauty of wood and the durability of plastic, and has the advantages of environmental protection, moisture resistance, and insect resistance. The design of a thickness of not less than 4 cm ensures that the composite board has sufficient rigidity and wear resistance, and can withstand various impacts and wear in daily use.

[0104] Specifically, in this embodiment, the upper surface of the composite board body 101 is covered with a wrapping layer 3 by a co-extrusion process, and the wrapping layer 3 is an ASA resin material layer. The ASA resin material layer is covered on the upper surface of the composite board body 101 by a co-extrusion process as the wrapping layer 3, which not only improves the wear resistance, weather resistance and UV resistance of the floor, but also makes the floor surface smoother, more beautiful, and easy to clean and maintain. The excellent performance of the ASA resin further extends the service life of the floor.

[0105] The above specific implementation details together constitute a complete design of a high-strength, high-wear-resistant, corrosion-resistant plate, which can exhibit excellent performance and long-lasting durability in a variety of applications.

[0106] Example 2

[0107] like Figure 6-Figure 7 As shown, the difference between this embodiment and embodiment 1 is that: this embodiment provides a preparation process of a high-strength, high-wear-resistant and anti-corrosion plate, comprising the following steps:

[0108] S1: Prepare raw materials for the composite plate (101), including the following raw materials in parts by weight:

[0109] 19 parts of corn stalks with a particle size of 100-200 mesh, 10 parts of wood flour with a particle size of 400-500 mesh, 58 parts of modified polypropylene, 15 parts of ethylene-vinyl acetate copolymer, 0.7 parts of silane coupling agent, 3 parts of modified filler, 2 parts of calcium stearate, 0.4 parts of antibacterial agent (silver ion antibacterial agent, purchased from Nanjing Tianshi Landun Biotechnology Co., Ltd., model: silver ion antibacterial agent-LD904) and 0.2 parts of antioxidant (model: Irganox1010, BASF).

[0110] The preparation method of modified polypropylene comprises the following steps:

[0111] (1) 1 part by weight of graphene oxide (graphene oxide sheet diameter is 0.5-5 μm, thickness is 0.8-1.2 nm, purchased from Xianfeng Nano) and 120 parts by weight of deionized water are mixed, ultrasonically dispersed, 0.3 parts by weight of silane coupling agent KH560 is added, mixed evenly, heated to 72° C., stirred for reaction for 2.5 hours, 0.15 parts by weight of hydrazine hydrate and 1.2 parts by weight of ammonia water are added, and reduction reaction is carried out under stirring for 3 hours, filtered and dried to obtain silane-modified reduced graphene oxide;

[0112] (2) 25 parts by weight of polypropylene were dissolved in 110 parts by weight of xylene at 132° C., and 2 parts by weight of silane-modified reduced graphene oxide were added. The mixture was stirred and reacted for 6 hours under heat preservation conditions, and vacuum dried to obtain modified polypropylene.

[0113] Polypropylene was purchased from Formosa Plastics (Ningbo) Co., Ltd.; model 1450T.

[0114] The ethylene-vinyl acetate copolymer includes ethylene-vinyl acetate copolymer A, ethylene-vinyl acetate copolymer B and ethylene-vinyl acetate copolymer C in a weight ratio of 1:1.3:0.6, the melt index of ethylene-vinyl acetate copolymer A is 7.5g / 10min, and the mass percentage of vinyl acetate unit is 26%; the melt index of ethylene-vinyl acetate copolymer A is 25g / 10min, and the mass percentage of vinyl acetate unit is 28%; the melt index of ethylene-vinyl acetate copolymer A is 150g / 10min, and the mass percentage of vinyl acetate unit is 19%. All are purchased from Formosa Plastics Industry (Ningbo) Co., Ltd.; models are 7470M, 7760H, and 7A50H.

[0115] The modified filler comprises the following steps:

[0116] (1) mixing titanium dioxide, lanthanum oxide and silicon dioxide in a weight ratio of 1.4:1:0.5 to obtain a mixed filler;

[0117] (2) mixing a mixed filler, a silane coupling agent KH560, ethanol and deionized water in a weight ratio of 1:0.2:22:38, heating and stirring at 82° C. for 4 h, cooling, filtering and washing to obtain a silane-modified mixed filler;

[0118] (3) A silane-modified mixed filler, nano-polytetrafluoroethylene (Japan Daikin F-104), polyvinyl pyrrolidone (molecular weight 2000Da) and a 45% by weight ethanol aqueous solution were mixed in a weight ratio of 1:12:0.3:70, dispersed evenly, and then spray-dried to obtain a modified filler.

[0119] The particle size of the titanium dioxide is 10-20 nm and the specific surface area is 30-100 m 2 / g; the particle size of lanthanum oxide is 30-50nm and the specific surface area is 20-40m 2 / g; the particle size of silicon dioxide is 10-20nm and the specific surface area is 200-250m 2 / g.

[0120] S2: preparing a raw material of a metal plate 201, that is, preparing a long strip of aluminum alloy plate having a recessed portion 202, a raised portion 203 and a through hole 204;

[0121] S3: Design a forming mold 4, wherein the forming mold 4 has a composite plate body forming cavity inside, and a cover plate 404 is detachably installed at one end of the forming mold 4, the cover plate 404 is used to block one end of the composite plate body forming cavity, and the cover plate 404 has a slot 405 for inserting a long strip of aluminum alloy plate, and a feed pipe 402 is fixedly installed on the outer wall of the forming mold 4 through a plurality of evenly arranged connecting pipes 401, the feed pipe 402 is connected to the interior of the composite plate body forming cavity through the plurality of connecting pipes 401, and a flange 403 connected to the interior of the feed pipe 402 is fixedly installed on the feed pipe 402;

[0122] It is worth mentioning that a column for forming the through groove 104 is fixedly installed in the composite plate molding cavity inside the molding mold 4, and the cover plate 404 can be fixed by screws, or a telescopic element, such as a hydraulic cylinder, can be fixedly installed on the outside of the molding mold 4, and a plug rod is installed on the piston rod of the hydraulic cylinder. The plug rod can pass through the molding mold 4 and be inserted into the socket on the side of the cover plate 404 to lock the cover plate 404.

[0123] S4: Assemble the molding die 4 and the extruder, and fix the flange 403 to the extrusion head of the extruder by bolts;

[0124] S5: the raw materials of the composite board body (101) in step S1 are mixed uniformly by a mixer, and then the uniformly mixed raw materials are melt-blended at 180° C. by a twin-screw extruder, and extruded into granules to obtain wood-plastic composite granules;

[0125] S6: After the wood-plastic composite pellets prepared in step S5 are added to the extruder in step S4 and heated and melted to a suitable temperature, one end of the long strip aluminum alloy plate is inserted into the composite plate forming cavity inside the forming mold 4 through the slot 405, and then the molten raw material is squeezed into the feed pipe 402 by the extruder and then enters the composite plate forming cavity inside the forming mold 4 through a plurality of evenly arranged connecting pipes 401;

[0126] S7: After the raw materials in the composite board forming cavity are formed, the cover plate 404 is removed, and then the formed wood-plastic composite board body together with the long strip aluminum alloy board body are taken out, and are quickly cooled and formed by a cooling device (such as a fan) to keep its shape and size stable;

[0127] S8: Subsequent processing: Cutting, trimming and subsequent processing are performed as needed to obtain finished high-strength, high-wear-resistant and anti-corrosion plates;

[0128] S9: Inspection and packaging: Carry out quality inspection on finished products, including appearance, size, and mechanical performance indicators. After passing the inspection, they will be packaged and put into storage.

[0129] Example 3

[0130] The difference between this embodiment and embodiment 1 is that this embodiment provides an application of a high-strength, high-wear-resistant, and anti-corrosion plate, which is applied to spliced ​​floors.

[0131] In summary, the high-strength, high-wear-resistant, anti-corrosion plate and its preparation process and application provided in this embodiment have the following advantages:

[0132] This high-strength, high-wear-resistant, and anti-corrosion board achieves excellent performance such as high strength, high wear resistance, and anti-corrosion through innovative designs such as integrated co-extrusion process, seamless splicing design, and concave-convex alternating structure of metal plate body. It has the advantages of easy installation, easy maintenance, and beautiful appearance. It can solve the problem that dust and garbage are easily accumulated in the connection gaps of traditional wood-plastic flooring, and even the phenomenon that people are easily tripped by the excessive connection gaps, which is very inconvenient. At the same time, it makes up for the shortcomings of traditional wood-plastic flooring in its own structural strength, bearing capacity, compression and deformation resistance, etc., as well as the common problems of thermal expansion and contraction and easy fracture.

[0133] By optimizing the formula and preparation process, the interface compatibility between wood fiber and resin matrix is ​​improved, making the composite material more uniform and dense, and reducing the occurrence of defects and cracks.

[0134] The preparation method is simple and efficient, easy to industrialize, and the product has low cost, good environmental protection, and broad market application prospects.

[0135] Comparative Example 1

[0136] The difference between this comparative example and Example 2 is that 58 parts of modified polypropylene and 15 parts of ethylene-vinyl acetate copolymer are replaced by 65 parts of modified polypropylene and 8 parts of ethylene-vinyl acetate copolymer.

[0137] Comparative Example 2

[0138] The difference between this comparative example and Example 2 is that the modified polypropylene is replaced by polypropylene, which is purchased from Formosa Plastics (Ningbo) Co., Ltd.; model 1450T. 2 parts by weight of graphene are added to the raw materials of the composite plate (101). The sheet diameter of the graphene oxide is 0.5-5 μm and the thickness is 0.8-1.2 nm. It is purchased from Xianfeng Nano.

[0139] Comparative Example 3

[0140] The difference between this comparative example and Example 2 is that the ethylene-vinyl acetate copolymer includes ethylene-vinyl acetate copolymer A, ethylene-vinyl acetate copolymer B and ethylene-vinyl acetate copolymer C in a weight ratio of 1:1:1, the melt index of ethylene-vinyl acetate copolymer A is 7.5g / 10min, and the mass percentage of vinyl acetate unit is 26%; the melt index of ethylene-vinyl acetate copolymer A is 25g / 10min, and the mass percentage of vinyl acetate unit is 28%; the melt index of ethylene-vinyl acetate copolymer A is 150g / 10min, and the mass percentage of vinyl acetate unit is 19%. All are purchased from Formosa Plastics Industry (Ningbo) Co., Ltd.; models 7470M, 7760H, 7A50H.

[0141] Comparative Example 4

[0142] The difference between this comparative example and Example 2 is that the melt index of ethylene-vinyl acetate copolymer A is 400 g / 10 min, and the mass percentage of vinyl acetate unit is 19%; the melt index of ethylene-vinyl acetate copolymer A is 5.5 g / 10 min, and the mass percentage of vinyl acetate unit is 26%; the melt index of ethylene-vinyl acetate copolymer A is 400 g / 10 min, and the mass percentage of vinyl acetate unit is 28%. All are purchased from Formosa Plastics Industry (Ningbo) Co., Ltd.; models 7B50H, 7470K, 7B60H.

[0143] Comparative Example 5

[0144] The difference between this comparative example and Example 2 is that titanium dioxide, lanthanum oxide and silicon dioxide are mixed in a weight ratio of 1:1:1 to obtain a mixed filler.

[0145] Comparative Example 6

[0146] The difference between this comparative example and Example 2 is that the modified filler comprises the following steps:

[0147] (1) mixing titanium dioxide, lanthanum oxide and silicon dioxide in a weight ratio of 1.4:1:0.5 to obtain a mixed filler;

[0148] (2) A mixed filler with a mass ratio of 1:7:0.02, a 55 wt % ethanol aqueous solution, and a silane coupling agent KH560 were mixed, stirred at 65° C. for 4 h, and the solid was filtered, washed, and dried to obtain a modified filler.

[0149] Comparative Example 7

[0150] The difference between this comparative example and Example 2 is that the particle size of the titanium dioxide is 40-70nm and the specific surface area is 20-60m 2 / g; the particle size of lanthanum oxide is 80-100nm and the specific surface area is 5-15m 2 / g; the particle size of silicon dioxide is 50-80nm and the specific surface area is 100-150m 2 / g.

[0151] Performance Testing

[0152] The raw materials of the composite board body (101) according to Example 2 and Comparative Examples 1-7 are mixed uniformly by a mixer, and then the uniformly mixed raw materials are melt-blended at 180° C. by a twin-screw extruder, extruded and granulated to obtain wood-plastic composite pellets; the wood-plastic composite pellets are added to the extruder, heated and melted to a suitable temperature, and cooled and shaped to prepare a board with a thickness of 27 mm. The performance of the board is tested with reference to GB17657-2013.

[0153] Percentage increase in boiling water resistance quality = (static bending strength after boiling water - static bending strength before boiling water) / static bending strength before boiling water * 100%.

[0154] Corrosion resistance test method: After inoculating Coriolus versicolor on potato dextrose agar (PDA) for 10 days, use a sterile punch to cut a mycelium block with a diameter of about 5 mm, inoculate it into the middle part of the river sand sawdust culture medium with fodder wood, and incubate it in a 28°C incubator for about 10 days. When the surface of the river sand sawdust culture medium is covered with mycelium, the sterilized board can be inoculated. After incubating the test bottle containing the board in an incubator at 28°C and 85% relative humidity for 12 weeks, take out the board, scrape off the surface mycelium and impurities, and bake it in an oven at 100±5°C to constant weight. Calculate the mass loss rate of the board before and after decay. The calculation formula = (mass of the board before corrosion - mass of the board after corrosion) / mass of the sample before corrosion * 100%.

[0155] Table 1 Performance test results

[0156]

[0157]

[0158] As shown in Table 1, the board prepared by the raw materials of Example 2 has excellent comprehensive performance. Comparative Example 1 changes the addition amount of modified polypropylene and ethylene-vinyl acetate copolymer, and the waterproof performance of the board decreases; Comparative Example 2 does not modify the polypropylene, which affects the antibacterial and anticorrosive properties of the board. Comparative Examples 3 and 4 have different ratios and raw material parameters of ethylene-vinyl acetate copolymer, which affects the boiling water resistance of the board. Comparative Examples 5 and 7 have different filler compositions and parameters, and Comparative Example 6 has different filler modification methods, which leads to a decrease in the wear resistance of the board.

[0159] Example 3

[0160] like Figure 8-10 As shown, the difference between this embodiment and embodiment 1-2 is that the high-strength, high-wear-resistant and anti-corrosion plate provided is a solid structure, which includes a solid substrate 5 and a lining plate 2 embedded in the substrate 5, and a plurality of trapezoidal grooves 501 are evenly distributed on the bottom of the solid substrate 5. The upper part of the solid substrate 5 is also coated with an ASA resin material layer, and card slots are provided on both sides of the solid substrate 5. The solid substrate 5 with a solid structure makes the overall strength of the high-strength, high-wear-resistant and anti-corrosion plate reach a higher level, and is more durable and less prone to damage.

[0161] The above are only preferred embodiments of the present invention, and are not intended to limit the implementation methods and protection scope of the present invention. Those skilled in the art should be aware that all solutions obtained by equivalent substitutions and obvious changes made using the description and illustrations of the present invention should be included in the protection scope of the present invention.

Claims

1. A high-strength, high-wear-resistant, anti-corrosion plate, characterized in that: include: A substrate (1) and a lining plate (2) embedded in the substrate (1), wherein: The base plate (1) comprises a composite plate body (101), and a plurality of the composite plate bodies (101) are spliced ​​together to form a spliced ​​floor.

2. The high-strength, high-wear-resistant, anti-corrosion plate according to claim 1, characterized in that: The lining plate (2) comprises a metal plate body (201), and the metal plate body (201) forms an integral structure with the composite plate body (101) through a co-extrusion process.

3. The high-strength, high-wear-resistant, anti-corrosion plate according to claim 1, characterized in that: A through hole (204) is provided on the surface of the metal plate (201).

4. The high-strength, high-wear-resistant, anti-corrosion plate according to claim 2, characterized in that: A long strip groove (102) penetrating through both ends of the composite plate body (101) is reserved on one side thereof, and a long strip convex strip (103) protruding outward is reserved on the other side of the composite plate body (101); the long strip convex strip (103) can be inserted into the long strip groove (102) by interference fit, and adjacent composite plates (101) are seamlessly spliced ​​by inserting the long strip convex strip (103) into the long strip groove (102).

5. The high-strength, high-wear-resistant, anti-corrosion plate according to claim 2, characterized in that: The metal plate body (201) extends in the direction of the long strip-shaped slot (102) to form a concave-convex alternating structure, and the formed recessed portion (202) and the formed raised portion (203) are respectively close to the upper and lower surfaces of the composite plate body (101), and the formed recessed portion (202) and the formed raised portion (203) do not protrude from the upper and lower surfaces of the composite plate body (101).

6. The high-strength, high-wear-resistant, anti-corrosion plate according to claim 5, characterized in that: The composite plate body (101) is evenly reserved with a plurality of through grooves (104) along the direction of the long strip-shaped slot (102), and the plurality of through grooves (104) are staggeredly arranged between adjacent recessed portions (202) and raised portions (203).

7. The high-strength, high-wear-resistant, anti-corrosion plate according to claim 6, characterized in that: The plurality of through grooves (104) are circular, elliptical, trapezoidal or square.

8. The high-strength, high-wear-resistant, anti-corrosion plate according to claim 5, characterized in that: A plurality of evenly arranged separation grooves (105) are reserved at the bottom of the composite plate body (101), and the length direction of the separation grooves (105) is consistent with the length direction of the long strip-shaped card slot (102).

9. The high-strength, high-wear-resistant, anti-corrosion plate according to claim 5, characterized in that: The cross-sections of the recessed portion (202) and the raised portion (203) perpendicular to the length direction of the long strip-shaped slot (102) are both trapezoidal, and through holes (204) are provided on the bottom wall and side walls of the recessed portion (202) and on the top wall and side walls of the raised portion (203).

10. The high-strength, high-wear-resistant, anti-corrosion plate according to claim 3, characterized in that: The through holes (204) are circular, elliptical, trapezoidal or square.

11. A process for preparing the high-strength, high-wear-resistant and anti-corrosion plate according to claim 10, characterized in that: The steps include: S1: Prepare raw materials for the composite plate (101), including the following raw materials in parts by weight: 18-20 parts of corn stalks with a particle size of 100-200 mesh, 8-12 parts of wood flour with a particle size of 400-500 mesh, 54-60 parts of modified polypropylene, 12-17 parts of ethylene-vinyl acetate copolymer, 0.6-0.9 parts of silane coupling agent, 1-4 parts of modified filler, 1-3 parts of calcium stearate, 0.2-0.5 parts of antibacterial agent and 0.1-0.3 parts of antioxidant; S2: preparing a raw material of a metal plate (201), that is, preparing a long strip of aluminum alloy plate having a recessed portion (202), a raised portion (203) and a through hole (204); S3: Design a molding die (4), wherein the molding die (4) has a composite plate molding cavity inside, and a cover plate (404) is detachably mounted on one end of the molding die (4), wherein the cover plate (404) is used to block one end of the composite plate molding cavity, and the cover plate (404) has a slot (405) for inserting a long strip of aluminum alloy plate, and a feed pipe (402) is fixedly mounted on the outer wall of the molding die (4) via a plurality of evenly arranged connecting pipes (401), wherein the feed pipe (402) is connected to the interior of the composite plate molding cavity via the plurality of connecting pipes (401), and a flange (403) connected to the interior of the feed pipe (402) is fixedly mounted on the feed pipe (402); S4: Assembling the molding die (4) and the extruder, and fixing the flange (403) to the extrusion head of the extruder by bolts; S5: the raw materials of the composite board body (101) in step S1 are mixed uniformly by a mixer, and then the uniformly mixed raw materials are melt-blended and granulated by a twin-screw extruder to obtain wood-plastic composite granules; S6: adding the wood-plastic composite pellets prepared in step S5 to the extruder in step S4 and heating and melting them to a suitable temperature, inserting one end of the long strip aluminum alloy plate into the composite plate forming cavity inside the forming mold (4) through the slot (405), and then using the extruder to squeeze the molten raw material into the feed pipe (402) and then into the composite plate forming cavity inside the forming mold (4) through a plurality of evenly arranged connecting pipes (401); S7: after the raw materials in the composite board forming cavity are formed, the cover plate (404) is removed, and then the formed wood-plastic composite board body together with the long strip aluminum alloy board body are taken out, and are rapidly cooled and formed by a cooling device to keep their shape and size stable; S8: Subsequent processing: Cutting, trimming and subsequent processing are performed as needed to obtain finished high-strength, high-wear-resistant and anti-corrosion plates; S9: Inspection and packaging: Carry out quality inspection on finished products, including appearance, size, and mechanical performance indicators. After passing the inspection, they will be packaged and put into storage.

12. An application of the high-strength, high-wear-resistant and anti-corrosion plate according to any one of claims 1 to 10, characterized in that: It is used for splicing panels.

Citation Information

Patent Citations

  • PVC (Polyvinyl Chloride)-lignin-sulfate wood-plastic composite material and preparation method thereof

    CN108384139A

  • Floor capable of being seamlessly spliced

    CN218028697U